Involvement of DAD1-like lipases in response to salt and osmotic stress in Arabidopsis thaliana - Ellinger, Dorothea (Landes Bioscience, 2010)
Acyl hydrolases remodel biological membranes and release signaling molecules in response to a variety of biotic and abiotic stresses. After wounding or pathogen treatment lipases are necessary to release fatty acids as substrate for jasmonate biosynthesis. In osmotic stressed tissue they maintain integrity and functionality of membranes and during senescence lipases destroy and recycle membranes. Recently the role of several acyl hydrolases including DEFECTIVE IN ANTHER DEHISCENCE1 (DAD1) and DAD1-like lipase, e.g., DONGLE (DGL) and the phospholipase A (PLA) PLA-Iγ1 in jasmonate biosynthesis after wounding were investigated and functional redundancy within this family has been stated. Here we report necessity of diverse DAD1-like lipases in response to salt and sorbitol treatment. The lipase PLA-Iγ1 and PLA-Iβ2, which were both impaired in wound response, were also affected in response to osmotic stress in seed germination assays. Based on our observations and interpretations of transcription analyses generated by AtGenExpress project we speculate about more general roles of the DAD1-like lipase in diverse biological processes.